Effectiveness of Qris on Payment Efficiency Systems in Perspective of Maslahah Mursalah - Bustamir, Aidil; Hidayati, Athi’; Febriyanti, Novi; Ritonga, Iskandar; Nurhayati, Nurhayati (International Journal Labs, 2025)
This quantitative study investigates the impact of QRIS financial literacy and e-wallet promotions on the cashless society phenomenon, while also exploring its social-religious implications through the lens of Maslahah. Using a mixed-method approach, the study collected data from East Java residents who had used QRIS or e-wallets at least once, through accidental sampling. Quantitative data were analyzed using SmartPLS 3.0, complemented by qualitative interviews. The results show that QRIS financial literacy has no significant effect on the growth of the cashless society. Although literacy levels are increasing, they are not consistently followed by QRIS usage due to the availability of diverse non-cash alternatives. In contrast, e-wallet promotions have a significant and positive influence on cashless behavior. Respondents are more likely to adopt e-wallets due to attractive promotions and the influence of their social environment. From a Maslahah perspective, the cashless society has the potential to deliver social and economic benefit but also poses risks—particularly if it fuels impulsive, non-beneficial consumption. Maslahah serves as a guiding framework, encouraging the cashless movement to align with values that promote communal well-being and ethical financial behavior. This study recommends that Bank Indonesia intensify financial education on QRIS to boost adoption. Meanwhile, e-wallet platforms should continue offering positive promotional strategies to enhance user engagement while aligning with Maslahah principles to ensure responsible usage.